USING THE ANGULAR CYLINDRICAL REFLEKTOR TO ADJAST THE SENSIVITY OF THE ULTRASONIK FLAW DETEKTOR - A. G. Lezhava; A. A. Pivovarchyk; A. S. Traihel (Литьë и металлургия)
The article analyzes the existing artificial reflectors are used to adjust the sensitivity of the ultrasonic flaw detectors. Noting their shortcomings, mainly related to the accuracy of manufacture. As an alternative, the angular cylindrical reflector. The influence of manufacturing error on the amplitude of the reflected signal. On the basis of the result proposed by the sensitivity setting method that eliminates the main drawback.